Genomics Reveals a Unique Clone of Burkholderia cenocepacia Harboring an Actively Excising Novel Genomic Island - Patil, Prashant P.; Mali, Swapna; Midha, Samriti; Gautam, Vikas; Dash, Lona; Kumar, Sunil; Shastri, Jayanthi; Singhal, Lipika; Patil, Prabhu B. (Frontiers in Microbiology, 2017)
Burkholderia cenocepacia is a clinically dominant form among the other virulent species of Burkholderia cepacia complex (Bcc). In the present study, we sequenced and analyzed the genomes of seven nosocomial Bcc isolates, five of which were isolated from the bloodstream infections and two isolates were recovered from the hospital setting during the surveillance. Genome-based species identification of the Bcc isolates using a type strain explicitly identified the species as B. cenocepacia. Moreover, single nucleotide polymorphism analysis revealed that the six isolates were clonal and phylogenetically distinct from the other B. cenocepacia. Comparative genomics distinctly revealed the larger genome size of six clonal isolates as well as the presence of a novel 107kb genomic island named as BcenGI15, which encodes putative pathogenicity-associated genes. We have shown that the BcenGI15 has an ability to actively excise from the genome and forming an extrachromosomal circular form suggesting its mobile nature. Surprisingly, a homologue of BcenGI15 was also present in the genome of a clinical isolate named Burkholderia pseudomallei strain EY1. This novel genetic element is present only in the variants of B. cenocepacia and B. pseudomallei isolates suggesting its interspecies existence in the main pathogenic species of the genus Burkholderia. In conclusion, the whole genome analysis of the genomically distinct B. cenocepacia clinical isolates has advanced our understanding of the epidemiology and evolution of this important nosocomial pathogen as well as its relatives.